Stress and the menopausal transition in Campeche, Mexico - Lynnette Leidy Sievert; Laura Huicochea-Gómez; Diana Cahuich-Campos; Dana-Lynn K; Daniel E. Brown (BMC, 2018)
Abstract Background Stress has been implicated as a factor in the presence and severity of symptoms during the menopausal transition. Our primary aim was to test the hypothesis that stress-sensitive biological measures and self-reported stress would be positively associated with a greater likelihood and intensity of hot flashes. Our secondary aim was to examine measures of stress in relation to the most often reported symptoms in Campeche, Mexico. We also hypothesized ethnic differences (Maya versus non-Maya) in relation to measures of stress and symptom reports. Methods Participants aged 40-60 (n = 305) were drawn from multiple sites across the city of San Francisco de Campeche to achieve a generally representative sample. Measures included C-reactive protein (CRP), an indicator of inflammation; Epstein-Barr virus antibodies (EBV-Ab), an indicator of immune function; the Perceived Stress Scale (PSS); a symptom checklist; anthropometric measures; and a questionnaire that elicited symptoms, ethnicity (based on language, birthplace, and last names of the woman, her parents, and her grandparents) and ten dimensions of socioeconomic status (SES). The relationships between symptoms and stress-sensitive biological and self-reported measures were examined in bivariate analyses, and with logistic and linear regressions. Results The twelve most common symptoms reported, in descending order of frequency, were tiredness, muscle and joint pain, nervous tension, problems concentrating, feeling depressed, difficulty sleeping, headaches, feeling of ants crawling on the skin, loss of interest in sex, urinary stress incontinence, hot flashes, and night sweats. PSS scores were significantly associated with the likelihood of seven symptoms (yes/no), and with the intensity of ten symptoms after controlling for ethnicity, SES, education, cohabitation status, parity, smoking, body mass index, and menopausal status. The stress-sensitive biological measures of immune function (EBV-Ab and CRP) were not significantly associated with midlife symptoms. The PSS was associated with more symptoms among the Maya (e.g., feeling nervous/tense and having difficulty concentrating) than non-Maya. Conclusion PSS scores were associated with the intensity, but not the likelihood, of hot flashes. Other symptoms were also associated with self-reported stress but not with physiological measures. Maya/non-Maya differences may indicate that either symptoms or stress were experienced and/or reported in culture-specific ways.